Plasticity in ZrB2 micropillars induced by anomalous slip activation. Issue 3 (February 2016) - Csanádi, Tamás; Szommer, Péter; Chinh, Nguyen Q.; Grasso, Salvatore; Dusza, Ján; Reece, Mike
Abstract: Room temperature deformation behaviors of ZrB2 micropillars, fabricated by focused ion beam technique from differently oriented grains of polycrystalline ZrB2, were investigated under micro compression. Considerable anisotropy was found showing ∼80% higher yield ( σ Y ) and rupture ( σ r ) stress values for the basal oriented pillars ( σ Y, basal =13.4 GPa, σ r, basal = 13.4 GPa ) compared to the prismatic pillars ( σ Y, prism = 6.4 GPa, σ r, prism = 7.6 GPa ) . Micro-scale plasticity was detected in prismatic oriented pillars, revealing the activation of the 10 1 ¯ 0 〈 11 2 ¯ 3 〉 type slip system both in the form of single- and multiple-slip which is anomalous for ZrB2 and has not been reported so far in the relevant literature.